2009
DOI: 10.1177/0959683609345081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of river capture on hydrography and water resources: case study of Ula and Katra catchments, south Lithuania

Abstract: Based on cartographic material from three time periods during the nineteenth and twentieth centuries, the impact of river capture, which started in the middle of the nineteenth century, on transformations of the watershed and hydrographic network of two Lithuanian rivers, Ula and Katra, is analysed. It has been determined that river capture conditioned marked transformations of water supply and distribution. As a result of the capture, the area of Ula catchment has increased by 62% and its mean discharge by 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…However, landscapes might change due to several phenomena such as erosion, tectonic motion, and volcanic activity. Such changes in the landscape are known to trigger local events called stream capture [12][13][14][15][16][17][18], which can affect the watershed. In what follows, we extend the recent work presented in Ref.…”
Section: Impact Of Perturbations In Two Dimensionsmentioning
confidence: 99%
“…However, landscapes might change due to several phenomena such as erosion, tectonic motion, and volcanic activity. Such changes in the landscape are known to trigger local events called stream capture [12][13][14][15][16][17][18], which can affect the watershed. In what follows, we extend the recent work presented in Ref.…”
Section: Impact Of Perturbations In Two Dimensionsmentioning
confidence: 99%
“…Geographers and geomorphologists have found that the evolution of watersheds is typically driven by local changes of the landscape [47]. These events can be triggered by various mechanisms like erosion [46,48,49], natural damming [8], tectonic motion [50][51][52], as well as volcanic activity [53]. Although rare, these local events can have a huge impact on the hydrological system [47][48][49]54].…”
Section: Impact Of Perturbation On Watershedsmentioning
confidence: 99%
“…These events can be triggered by various mechanisms like erosion [46,48,49], natural damming [8], tectonic motion [50][51][52], as well as volcanic activity [53]. Although rare, these local events can have a huge impact on the hydrological system [47][48][49]54]. For example, it was shown that a local height change of less than two meters at a location close to the Kashabowie Provincial Park, some kilometers North of the US-Canadian border, can trigger a displacement in the watershed such that the area enclosed by the original and the new watersheds is about 3730 km 2 [55].…”
Section: Impact Of Perturbation On Watershedsmentioning
confidence: 99%
“…The highest altitudes are distributed in the northeast of the territory, where landforms of the Middle Pleistocene Medininkai (Warthe) glaciation are widespread (Baltrūnas et al, 2007). Prior to 1840, the whole area was drained via the River Katra westward (Linkevičienė, 2009), and the direction of the abovementioned Ūla inlet was opposite to that of the present day. The terrain in the area between the present Katra and Ūla inlet upper reaches is rather flat (altitudes vary within 1 m at most parts of the territory), i.e.…”
Section: Terrain Of the Study Areamentioning
confidence: 99%